The effects of deep-level defects on the electrical properties of Cd0.9Zn0.1Te crystals*Project supported by the National Natural Science Foundation of China (No. 51502234) and the Scientific Research Plan Projects of Shaanxi Provincial Department of Education of China (No. 15JS040). (June 2017) - Wang, Pengfei; Nan, Ruihua; Jian, Zengyun
Abstract: The deep-level defects of CdZnTe (CZT) crystals grown by the modified vertical Bridgman (MVB) method act as trapping centers or recombination centers in the band gap, which have significant effects on its electrical properties. The resistivity and electron mobility–lifetime product of high resistivity Cd0.9 Zn0.1 Te wafer marked CZT1 and low resistivity Cd0.9 Zn0.1 Te wafer marked CZT2 were tested respectively. Their deep-level defects were identified by thermally stimulated current (TSC) spectroscopy and thermoelectric effect spectroscopy (TEES) respectively. Then the trap-related parameters were characterized by the simultaneous multiple peak analysis (SIMPA) method. The deep donor level ( E DD ) dominating dark current was calculated by the relationship between dark current and temperature. The Fermi-level was characterized by current–voltage measurements of temperature dependence. The width of the band gap was characterized by ultraviolet-visible-infrared transmittance spectroscopy. The results show the traps concentration and capture cross section of CZT1 are lower than CZT2, so its electron mobility–lifetime product is greater than CZT2. The Fermi-level of CZT1 is closer to the middle gap than CZT2. The degree of Fermi-level pinned by E DD of CZT1 is larger than CZT2. It can be concluded that the resistivity of CZT crystals increases as the degree of Fermi-level pinned near the middle gap by the deep donor level enlarges.